Policy & social work practice - Evans, Antony; Keating, Frank (Los Angeles : SAGE, 2016)
Editors Evans and Keating present readers with a collection of academic essays designed to allow for critical thinking regarding the relationship between policy and practice in social work. The editors argue that social policy is central to social work practice. The ten contributions that make up the text focus on discretion in history and the development of social work, social work education and training as a policy issue, the development of safeguarding in children's services, and many other related subjects. The editors are both faculty members of the University of London in the UK.
Social Work and Policy Introduction Discretion in the history and development of social work Social Work Education and Training as a policy issue Prevention and protection: the development of safeguarding in children's services Children like ours? Policy and practice responses to children looked after Personalisation Mental capacity and social policy Social welfare policy in racialised contexts International social work: understanding social work within social policy systems Domestic Violence: UK and Australian developments Local policy in a global context: regimes of risk in mental health policy and practice -- the community treatment orders Concluding thoughts: the interface between social policy and social work
Includes bibliographical references and index.
Keywords: Social policy; Social service; Social service -- Government policy; Social service; Socialt arbete; Great Britain